The regulation of healthcare professionals : law, principle, and process - Glynn, Joanna; Gomez, David (London : Sweet & Maxwell, 2012)
This title covers the entire healthcare regulatory cycle: from the regulation of students trainging for the healthcare professions; through registration and renewal of registration, including a thorough examination of the principles and case law relating to health, good character, and the relevant European law.
Includes bibliographical references and index.
Keywords: Medical laws and legislation -- United kingdom